High-flexibility heat-conducting gasket and preparation method thereof

Prepared by cross-linking of end vinyl side chain vinyl silicone oil with end hydrogen-containing silicone oil, combining cross-linked fibers and carbon nanotubes and core-shell aluminum ball fillers, an efficient three-dimensional thermal conductivity network is formed, solving the problem of insufficient flexibility of thermal gaskets , achieving efficient heat conduction and excellent flexibility.

CN119463503AActive Publication Date: 2025-02-18SUZHOU BAIMIN ELECTRONIC MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411693776.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

While improving thermal conductivity, existing thermal gaskets have poor flexibility and are difficult to adapt to complex surfaces, affecting the heat conduction effect.

Method used

The end vinyl side chain vinyl silicone oil and end hydrogen-containing silicone oil are used for cross-linking, combining cross-linked fibers and carbon nanotubes with core-shell aluminum ball fillers as thermal fillers to form an efficient three-dimensional thermal conductivity network.

Benefits of technology

It realizes the efficient thermal conduction performance and excellent flexibility of the thermal gasket, which can effectively disperse stress, maintain shape, adapt to complex surfaces, and improve heat conduction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151626520000051
    Figure BDA0005151626520000051
  • Figure BDA0005151626520000071
    Figure BDA0005151626520000071
  • Figure BDA0005151626520000101
    Figure BDA0005151626520000101
Patent Text Reader

Abstract

The invention relates to the technical field of heat-conducting materials, and particularly discloses a high-flexibility heat-conducting gasket and a preparation method thereof. The high-flexibility heat-conducting gasket is prepared from the following raw materials in parts by weight: 23 to 46 parts of vinyl-terminated side chain vinyl silicone oil, 9 to 15 parts of hydrogen-terminated silicone oil, 5 to 10 parts of vinyl MQ silicon resin, 11 to 17 parts of cross-linked fiber, 0.3 to 1.8 parts of platinum catalyst, 1 to 5 parts of cross-linking agent, 0.3 to 1.8 parts of inhibitor and 58 to 89 parts of heat-conducting filler. The heat-conducting filler comprises a carbon nanotube and a core-shell aluminum ball filler in a mass ratio of 1: (5-9). The high-flexibility heat-conducting gasket can be used for heat management in electronic packaging and has excellent heat conductivity and flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal conductive materials, and more specifically, to a highly flexible thermal conductive gasket and a preparation method thereof. Background Art

[0002] With the rapid development of electronic information technology and the continuous upgrading of modern high-end electronic products, electronic equipment is increasingly developing towards high integration and high power, which also leads to a significant increase in the heat flux density of electronic components and a significant increase in the heat generated by electronic equipment. Therefore, thermal management in electronic packaging has become a major concern for electronic components.

[0003] Thermal pads are materials that provide heat conduction channels by filling the air gap between heat generating devices and heat sinks or metal bases. They are widely used to dissipate heat generated by electronic devices such as mobile phones, computers, servers, etc. High-performance thermal pads not only need to have excellent thermal conductivity, but also need to have good flexibility and compression resilience to cover and fill uneven surfaces.

[0004] With respect to the above-mentioned related technologies, the inventors found that the common thermally conductive gaskets on the market are mainly based on silica gel, which is prepared by various processes after adding thermally conductive fillers. Some thermally conductive gaskets have improved the thermal conductivity of the thermally conductive gaskets to a certain extent, but due to the large amount of thermally conductive fillers added or the low compatibility between the choice of thermally conductive fillers and other raw materials, the thermally conductive gaskets have poor flexibility and are difficult to adapt to surfaces of complex shapes, affecting the effect and efficiency of the thermally conductive gaskets in the heat conduction process. Some thermally conductive gaskets have good flexibility, but low thermal conductivity and cannot meet the problem of efficient heat dissipation. Summary of the invention

[0005] In order to improve the thermal conductivity of a thermally conductive gasket while ensuring that the thermally conductive gasket has excellent flexibility, the present application provides a highly flexible thermally conductive gasket and a preparation method thereof.

[0006] In a first aspect, the present application provides a highly flexible thermally conductive gasket, which adopts the following technical solution: A highly flexible thermally conductive pad, wherein the raw materials include, by weight, 23-46 parts of vinyl-terminated side-chain vinyl silicone oil, 9-15 parts of hydrogen-terminated silicone oil, 5-10 parts of vinyl MQ silicone resin, 11-17 parts of cross-linked fibers, 0.3-1.8 parts of platinum catalyst, 1-5 parts of cross-linking agent, 0.3-1.8 parts of inhibitor and 58-89 parts of thermally conductive filler; The thermal conductive filler comprises carbon nanotubes and core-shell aluminum ball fillers in a mass ratio of 1:(5-9).

[0007] The inventors have found that the thermally conductive gaskets prepared by selecting vinyl-terminated side-chain vinyl silicone oil and hydrogen-terminated silicone oil have better flexibility. This may be because the structure of vinyl-terminated side-chain vinyl silicone oil contains siloxane segments and side-chain vinyl-containing segments, and when combined with hydrogen-terminated silicone oil, it can simultaneously achieve certain chain extension and cross-linking. In particular, the two segments in the vinyl silicone oil exist in block form, and the cross-linked structure generated after the reaction of the terminal group and the side group vinyl ensures a certain amount of free space for the linear segment. At the same time, the cross-linking points of the cross-linked segment are uniform and dense, which makes the thermally conductive gasket not only have the softness and elasticity of linear resins, but also the network structure obtained by cross-linking can better disperse stress when subjected to external force, and can quickly restore its original shape when deformed by force. Therefore, the gasket prepared by cross-linking vinyl-terminated side-chain vinyl silicone oil and hydrogen-terminated silicone oil exhibits good flexibility and resilience.

[0008] The addition of cross-linked fibers further promotes the interaction between the silicone oil raw materials. The cross-linked fibers have excellent flexibility and elasticity, and can improve the flexibility and elasticity of the gasket. The inventors have found that in the cross-linking system of the present application, the effect of adding cross-linked fibers is particularly prominent. This may be because the cross-linked fibers are more freely dispersed in the above-mentioned molecular cross-linking network, and the cross-linked fibers can effectively fill the stresses in different directions when receiving stresses in different directions. When the thermally conductive gasket is used to cover and fill the surface gaps of the heating device, it effectively disperses the stresses from different directions, prevents the gasket from breaking or deforming due to stress concentration, and enables the thermally conductive gasket to better fit the tiny gaps on the surface of the heating device.

[0009] Carbon nanotubes and core-shell aluminum ball fillers are both excellent fillers with excellent thermal conductivity. Adding them to silicone oil as thermal conductive fillers can effectively increase the viscosity of the mixed slurry. During the molding process of the thermal conductive gasket, the spherical aluminum filler can be evenly distributed between the carbon nanotubes. On the one hand, it can make the thermal conductive gasket have better fluidity and dispersibility during the molding process, significantly reducing the problem of carbon nanotubes entangled and agglomerated with each other in the liquid slurry. On the other hand, the spherical aluminum filler can squeeze the carbon nanotubes to a certain extent during the molding process of the thermal conductive gasket, making the curved carbon nanotubes tend to be straight, further enhancing the one-dimensional directional arrangement effect of the carbon nanotubes, and forming a more effective heat conduction channel inside the thermal conductive gasket, thereby further improving the thermal conductivity efficiency of the thermal conductive gasket.

[0010] Optionally, the core-shell aluminum ball filler is a core-shell structure of spherical metal aluminum powder wrapped by alumina, and the preparation method of the core-shell aluminum ball filler comprises the following steps: Spherical aluminum powder is added into anhydrous ethanol for ultrasonic treatment, and then centrifuged, dried and ground to form pretreated aluminum balls; the pretreated aluminum balls are heated to 300-500° C. in an air atmosphere and calcined for 6-8 hours to form a dense aluminum oxide layer on the surface of the pretreated aluminum balls, and the pretreated aluminum balls are obtained after cooling.

[0011] By adopting the above technical solution, metal aluminum has excellent thermal conductivity, and alumina has good electrical insulation in addition to thermal conductivity. Through self-passivation, a layer of dense alumina layer is wrapped around the metal aluminum microspheres as the core skeleton to form a core-shell aluminum ball filler. The core-shell aluminum ball filler combines the excellent thermal conductivity of metal aluminum with the electrical insulation properties of ceramic materials, so that the thermal conductive gasket has higher thermal conductivity while improving electrical insulation, increasing electrical safety and broadening the application field of the thermal conductive gasket.

[0012] Optionally, the raw materials of the cross-linked fiber include 40-55 parts of polyethylene glycol, 15-25 parts of Toluene diisocyanate, 0.2-0.6 parts of dibutyltin dilaurate and 5-10 parts of chain extender.

[0013] Optionally, the chain extender is an amino chain extender, and the amino chain extender is selected from any one or more combinations of 4,4'-methylene-bis(3-chloro-2,6-diethylaniline), ethylenediamine, dimethylthiotoluene diamine and triethylenetetramine.

[0014] By adopting the above technical solution, amino chain extenders are used to extend the chain in waterborne polyurethane, thereby enhancing the flexibility and plasticity of the cross-linked fibers prepared from waterborne polyurethane, improving the interfacial bonding strength, providing favorable conditions for efficient heat transfer, and reducing interfacial thermal resistance. On the other hand, it can significantly increase the flexibility and activity of the molecular chain and improve the flexibility of the thermal conductive gasket.

[0015] Optionally, the method for preparing the cross-linked fiber comprises the following steps: Mix polyethylene glycol and toluene diisocyanate, heat and stir at 80-100°C in an inert gas atmosphere, cool to 70-80°C, add an amino chain extender, continue stirring to perform chain extension and curing cross-linking reaction, and obtain a polyurethane prepolymer; Pour the polyurethane prepolymer into deionized water and stir to obtain a polyurethane stock solution; The polyurethane stock solution is matured, and then dry-spun to obtain cross-linked fibers.

[0016] By adopting the above technical solution, the preparation of cross-linked fibers from waterborne polyurethane is more environmentally friendly, and the formed cross-linked structure can effectively limit the movement of molecular chains, making the material more compact, reducing the volatilization of small molecules, reducing pores and channels, and reducing the release of volatile substances. This helps to reduce the volatile organic compounds (VOCs) released by the thermal pad during use, thereby reducing harm to the environment and human body. In addition, the introduction of polyethylene glycol segments can further improve the flexibility of the fiber, which is conducive to improving the flexibility of the pad.

[0017] Optionally, the cross-linking agent is silane coupling agent KH-560.

[0018] Optionally, the inhibitor is selected from acetylenic alcohol compounds or cyclic siloxane oligomers containing olefin groups.

[0019] In a second aspect, the present application provides a method for preparing a highly flexible thermally conductive gasket, using the following technical solution: A method for preparing a highly flexible thermally conductive gasket, comprising the following steps: The carbon nanotubes and core-shell aluminum ball fillers are mixed to form a thermal conductive filler, and then mixed with terminal vinyl side chain vinyl silicone oil, terminal hydrogen silicone oil, vinyl MQ silicone resin, cross-linked fiber, cross-linking agent and inhibitor, stirred evenly, heated at 120-150° C., and vacuum reacted for 6-8 hours to obtain a blend; After the blend is cooled to room temperature, a platinum catalyst is added, stirred, and vacuum reacted for 10-15 minutes, and then hot vulcanized and formed at 120-130°C to obtain the product.

[0020] Optionally, the carbon nanotubes are pretreated as follows before being mixed with the core-shell aluminum sphere filler: The carbon nanotubes are placed in an acid solution and ultrasonicated at 60-80°C for 4-8 hours, and then washed, filtered and dried to obtain acid-treated carbon nanotubes; Add the acid-treated carbon nanotubes to the acetone solution and stir evenly, then add the epoxy resin, continue stirring, and then heat to 120-150°C for reaction for 2-3 hours. After washing, filtering and drying, the pretreated carbon nanotubes are obtained. The mass ratio of the epoxy resin added to the acid-treated carbon nanotubes is (80-120):1.

[0021] By adopting the above technical solution, epoxy groups are introduced on the surface of carbon nanotubes, and the compatibility between carbon nanotubes and silicone oil, silicone resin and cross-linked fibers is significantly increased through chemical reactions between chemical bonds, forming a stronger interface bonding force with other raw materials. This allows a tighter structure to be formed inside the gasket, reducing the interface thermal resistance. At the same time, the dispersion of carbon nanotubes in the three-dimensional network structure formed in the thermally conductive gasket is further improved, significantly reducing the phenomenon of carbon nanotubes entangled and agglomerated with each other, and further improving the thermal conductivity efficiency of carbon nanotubes as thermally conductive fillers.

[0022] In summary, this application has the following beneficial effects: 1. The present application adopts terminal vinyl side chain vinyl silicone oil and terminal hydrogen silicone oil to form a three-dimensional cross-linked structure, which cooperates with the cross-linked fibers to form a three-dimensional thermal conductive network inside the thermal conductive gasket. It not only forms an efficient heat conduction channel inside the thermal conductive gasket, but also maintains excellent flexibility and resilience. It can better disperse stress from different directions when subjected to external force, and can quickly restore its original shape when deformed by force. It can better fit with the protrusions and tiny gaps on the surface of electronic components at the microscopic level, reduce the presence of air, and further improve the heat conduction efficiency.

[0023] 2. In this application, core-shell aluminum ball fillers formed by carbon nanotubes and alumina wrapped metal aluminum are used as thermal conductive fillers, which effectively improves the fluidity and dispersibility between the raw material mixed slurry during the preparation and molding process of the thermal conductive gasket, and significantly reduces the problem of carbon nanotubes entangled and agglomerated with each other in the liquid slurry. At the same time, the spherical core-shell aluminum ball fillers enhance the one-dimensional directional arrangement effect of the carbon nanotubes, forming a more efficient thermal conductive channel.

[0024] 3. The core-shell aluminum ball filler of the present application forms an aluminum oxide layer on the surface of metallic aluminum, combining the excellent thermal conductivity of metal materials and the electrical insulation properties of ceramic materials, so that the thermal conductive gasket has higher thermal conductivity while improving electrical insulation, ensuring electrical safety. DETAILED DESCRIPTION

[0025] The following examples further illustrate the present application in detail.

[0026] raw material Unless otherwise specified, the raw materials used in the examples and comparative examples of this application are all commercially available products, specifically: Vinyl-terminated side-chain vinyl silicone oil, selected from Shandong Dayi Chemical, DY-V421, with an average vinyl content of 0.05 mol / 100 g; End-hydrogenated silicone oil, selected from Shandong Dayi Chemical, DY-H201, with a hydrogen content of 0.05%; Vinyl MQ silicone resin, selected from Shandong Dayi Chemical, DY-VMQ101; Polyethylene glycol, selected from Hangzhou Electrochemical Group Auxiliary Chemical Co., Ltd., PEG-400; Toluene diisocyanate, selected from Shanghai Yuanye Biotechnology Co., Ltd., T135411; Dibutyltin dilaurate, selected from Jieshikai, KA728361; Dimethylthiotoluenediamine, selected from Congzhong Chemical Industry, 17005; Platinum catalyst, selected from Xiyi Chemical, PT-2000; 1-Alkynylcyclohexanol, selected from Shanghe Chemical Technology, CAS: 78-27-3; Tetravinyltetramethylcyclotetrasiloxane, selected from Dixin Chemical, CAS: 2554-06-5; The cross-linking agent is silane coupling agent KH-560, selected from Shanghe Chemical Technology; Carbon nanotubes, length 5-15 μm, diameter 8-20 nm, analytical grade; Spherical aluminum powder, purity ≥99.5%, average particle size 5μm; Spherical alumina powder, purity ≥99.9%, average particle size 5μm; Epoxy resin, selected from Haihong Chemical, E51E44.

[0027] Preparation Example 1.1-1.5 of Cross-linked Fiber Preparation Example 1.1 Cross-linked fibers, the raw materials and amounts are shown in Table 1, wherein the chain extender is an amino chain extender, dimethylthiotoluene diamine; Table 1 The method for preparing the cross-linked fiber comprises the following steps: S1: polyethylene glycol and toluene diisocyanate are mixed, heated and stirred at 80°C in a N2 atmosphere for 3 hours, and then the amino chain extender is added after the temperature is reduced to 70°C, and the mixture is stirred for 1 hour to perform chain extension and curing cross-linking reaction to obtain a polyurethane prepolymer; S2: Pour the polyurethane prepolymer into 150 mL of deionized water and stir at a speed of 8000 rpm in a high-speed stirrer for 1 h to obtain a polyurethane stock solution; S3: The polyurethane stock solution is matured, and after maturation, dry spinning is performed to obtain cross-linked fibers.

[0028] Preparation Example 1.2 The cross-linked fiber is different from the preparation example 1.1 in that the raw materials and amounts are as shown in Table 1. The preparation method thereof comprises the following steps: S1: polyethylene glycol and toluene diisocyanate are mixed, heated and stirred at 100° C. in a N2 atmosphere for 2 h, cooled to 80° C., an amino chain extender is added, and stirring is continued for 1 h to perform chain extension and curing cross-linking reaction to obtain a polyurethane prepolymer; S2: Pour the polyurethane prepolymer into 150 mL of deionized water and stir at a speed of 8000 rpm in a high-speed stirrer for 1 h to obtain a polyurethane stock solution; S3: The polyurethane stock solution is matured, and after maturation, dry spinning is performed to obtain cross-linked fibers.

[0029] Preparation Example 1.3 The cross-linked fiber is different from the preparation example 1.1 in that the raw materials and amounts are as shown in Table 1. The preparation method thereof comprises the following steps: S1: polyethylene glycol and toluene diisocyanate were mixed, heated and stirred at 100° C. in a N2 atmosphere for 2.5 h, and then the amino chain extender was added after the temperature was lowered to 70° C., and the mixture was stirred for 1 h to perform chain extension and curing cross-linking reaction to obtain a polyurethane prepolymer; S2: Pour the polyurethane prepolymer into 150 mL of deionized water and stir at a speed of 8000 rpm in a high-speed stirrer for 1 h to obtain a polyurethane stock solution; S3: The polyurethane stock solution is matured, and after maturation, dry spinning is performed to obtain cross-linked fibers.

[0030] Preparation Example 1.4 The cross-linked fiber is different from the preparation example 1.1 in that the raw materials and amounts are as shown in Table 1. The preparation method thereof comprises the following steps: S1: polyethylene glycol and toluene diisocyanate are mixed, heated and stirred at 90°C in a N2 atmosphere for 2 hours, cooled to 80°C, an amino chain extender is added, and stirring is continued for 1 hour to perform chain extension and curing cross-linking reaction to obtain a polyurethane prepolymer; S2: Pour the polyurethane prepolymer into 150 mL of deionized water and stir at a speed of 8000 rpm in a high-speed stirrer for 1 h to obtain a polyurethane stock solution; S3: The polyurethane stock solution is matured, and after maturation, dry spinning is performed to obtain cross-linked fibers.

[0031] Preparation Example 1.5 The cross-linked fiber is different from Preparation Example 1.1 in that the chain extender in the raw material is 1,4-butanediol, and the other steps are the same as Preparation Example 1.1.

[0032] Preparation Examples 2.1-2.3 of Core-Shell Aluminum Ball Fillers Preparation Example 2.1 The core-shell aluminum ball filler is a core-shell structure of spherical aluminum powder wrapped by aluminum oxide. The average particle size of the spherical aluminum powder is 5 μm. The preparation method thereof comprises the following steps: S1: Spherical aluminum powder was added to anhydrous ethanol and completely dispersed, ultrasonically treated for 48 hours, then centrifuged at 3500 rpm for 30 minutes, dried for 4 hours, and then ground to form pretreated aluminum balls; S2: The pretreated aluminum ball is placed in a ceramic crucible under air atmosphere, heated to 300°C and calcined for 8 hours to form a dense aluminum oxide layer on the surface of the pretreated aluminum ball. After cooling, the aluminum oxide layer is obtained with a thickness of 9 nm.

[0033] Preparation Example 2.2 The core-shell aluminum ball filler is different from the preparation example 2.1 in that its preparation method comprises the following steps: S1: Spherical aluminum powder was added to anhydrous ethanol and completely dispersed, ultrasonically treated for 48 hours, then centrifuged at 3500 rpm for 30 minutes, dried for 4 hours, and then ground to form pretreated aluminum balls; S2: The pretreated aluminum ball is placed in a ceramic crucible under air atmosphere, heated to 400°C and calcined for 7 hours to form a dense aluminum oxide layer on the surface of the pretreated aluminum ball. After cooling, the aluminum oxide layer is obtained with a thickness of 7 nm.

[0034] Preparation Example 2.3 The core-shell aluminum ball filler is different from the preparation example 2.1 in that its preparation method comprises the following steps: S1: Spherical aluminum powder was added to anhydrous ethanol and completely dispersed, ultrasonically treated for 48 hours, then centrifuged at 3500 rpm for 30 minutes, dried for 4 hours, and then ground to form pretreated aluminum balls; S2: The pretreated aluminum ball is placed in a ceramic crucible under air atmosphere, heated to 500°C and calcined for 6 hours to form a dense aluminum oxide layer on the surface of the pretreated aluminum ball. After cooling, the aluminum oxide layer is obtained with a thickness of 5 nm. Example

[0035] Example 1 A highly flexible thermally conductive gasket, the dosage of each raw material is shown in Table 2, wherein the cross-linked fiber is obtained by Preparation Example 1.1; the thermally conductive filler is a carbon nanotube and a core-shell aluminum ball filler in a mass ratio of 1:5, and the core-shell aluminum ball filler is obtained by Preparation Example 2.1; the inhibitor is an alkynol compound, 1-alkynylcyclohexanol.

[0036] Table 2 The above-mentioned method for preparing a highly flexible thermally conductive gasket comprises the following steps: S1: mixing carbon nanotubes and core-shell aluminum ball fillers to form a thermal conductive filler, and then mixing with terminal vinyl side chain vinyl silicone oil, terminal hydrogen silicone oil, vinyl MQ silicone resin, cross-linked fiber, cross-linking agent and inhibitor, stirring evenly, heating at 120° C., evacuating to a vacuum degree of -0.1 MPa, reacting for 8 hours, and obtaining a blend; S2: After cooling the blend to room temperature, add platinum catalyst, stir, evacuate to a vacuum degree of -0.1 MPa, react for 15 minutes, and then perform hot vulcanization molding on a flat vulcanizer at 10 MPa and 130°C to obtain the product.

[0037] Example 2 A highly flexible thermally conductive gasket, which differs from Example 1 in that the amounts of the raw materials are as shown in Table 2, wherein the cross-linked fibers are obtained from Preparation Example 1.2; the thermally conductive filler is a carbon nanotube and a core-shell aluminum ball filler in a mass ratio of 1:7; the inhibitor is an olefin-containing cyclic siloxane oligomer, tetravinyltetramethylcyclotetrasiloxane; The above-mentioned method for preparing a highly flexible thermally conductive gasket comprises the following steps: S1: carbon nanotubes and core-shell aluminum ball fillers are mixed to form a thermal conductive filler, and then mixed with terminal vinyl side chain vinyl silicone oil, terminal hydrogen silicone oil, vinyl MQ silicone resin, cross-linked fiber, cross-linking agent and inhibitor, stirred evenly, heated at 140°C, evacuated to a vacuum degree of -0.1 MPa, reacted for 6 hours, and obtained a blend; S2: After cooling the blend to room temperature, add platinum catalyst, stir, evacuate to a vacuum degree of -0.1 MPa, react for 15 minutes, and then perform hot vulcanization molding on a flat vulcanizer at 10 MPa and 120°C to obtain the product.

[0038] Example 3 A highly flexible thermally conductive gasket, which differs from Example 1 in that the amounts of the raw materials are as shown in Table 2, wherein the cross-linked fibers are obtained from Preparation Example 1.3; the thermally conductive filler is a carbon nanotube and a core-shell aluminum ball filler in a mass ratio of 1:9; The above-mentioned method for preparing a highly flexible thermally conductive gasket comprises the following steps: S1: mixing carbon nanotubes and core-shell aluminum ball fillers to form a thermal conductive filler, and then mixing with terminal vinyl side chain vinyl silicone oil, terminal hydrogen silicone oil, vinyl MQ silicone resin, cross-linked fiber, cross-linking agent and inhibitor, stirring evenly, heating at 150° C., evacuating to a vacuum degree of -0.1 MPa, reacting for 6 hours, and obtaining a blend; S2: After cooling the blend to room temperature, add platinum catalyst, stir, evacuate to a vacuum degree of -0.1 MPa, react for 10 minutes, and then perform hot vulcanization molding on a flat vulcanizer at 10 MPa and 130°C to obtain.

[0039] Example 4 A highly flexible thermally conductive gasket, which differs from Example 1 in that the amounts of the raw materials are as shown in Table 2, wherein the cross-linked fibers are obtained from Preparation Example 1.4; the thermally conductive filler is a carbon nanotube and a core-shell aluminum ball filler in a mass ratio of 1:6; The above-mentioned method for preparing a highly flexible thermally conductive gasket comprises the following steps: S1: mixing carbon nanotubes and core-shell aluminum ball fillers to form a thermal conductive filler, and then mixing with terminal vinyl side chain vinyl silicone oil, terminal hydrogen silicone oil, vinyl MQ silicone resin, cross-linked fiber, cross-linking agent and inhibitor, stirring evenly, heating at 150° C., evacuating to a vacuum degree of -0.1 MPa, reacting for 7 hours, and obtaining a blend; S2: After cooling the blend to room temperature, add platinum catalyst, stir, evacuate to a vacuum degree of -0.1 MPa, react for 15 minutes, and then perform hot vulcanization molding on a flat vulcanizer at 10 MPa and 120°C to obtain the product.

[0040] Example 5 A highly flexible thermally conductive gasket, which differs from Example 1 in that the cross-linked fibers in the raw material are obtained from Preparation Example 1.5, and the other steps are the same as Example 1.

[0041] Example 6 A highly flexible thermally conductive gasket, which differs from Example 1 in that the core-shell aluminum ball filler in the raw material is obtained from Preparation Example 2.2, and the other steps are the same as Example 1.

[0042] Example 7 A highly flexible thermally conductive gasket, which differs from Example 1 in that the core-shell aluminum ball filler in the raw material is obtained from Preparation Example 2.3, and the other steps are the same as Example 1.

[0043] Example 8 A highly flexible thermally conductive gasket, which differs from Example 1 in that the core-shell aluminum ball filler in the raw material is spherical aluminum oxide powder, and the other steps are the same as Example 1.

[0044] Example 9 A highly flexible thermally conductive gasket, which differs from Example 1 in that the core-shell aluminum ball filler in the raw material is spherical metal aluminum powder, and the other steps are the same as Example 1.

[0045] Example 10 A highly flexible thermally conductive gasket, which differs from Example 1 in that the core-shell aluminum ball filler in the raw material is spherical metal aluminum powder and spherical metal aluminum powder in a mass ratio of 1:3, and the other steps are the same as Example 1.

[0046] Embodiment 11 A highly flexible thermally conductive gasket, which differs from Example 1 in that the carbon nanotubes are pretreated as follows before being mixed with the core-shell aluminum ball filler: S1: placing carbon nanotubes in a mixed acid solution of H2SO4 / HNO3 with a volume ratio of 3:1, ultrasonicating at 60°C for 8h, and then washing, filtering and drying to obtain acid-treated carbon nanotubes; S2: Add the acid-treated carbon nanotubes to the acetone solution, stir evenly, then add the epoxy resin, continue stirring, and then heat to 120°C for reaction for 3 hours. After washing, filtering and drying, the pretreated carbon nanotubes are obtained. The mass ratio of the added epoxy resin to the acid-treated carbon nanotubes is 12:1. The other steps are the same as in Example 1.

[0047] Example 12 A highly flexible thermally conductive gasket, which differs from Example 1 in that the carbon nanotubes are pretreated as follows before being mixed with the core-shell aluminum ball filler: S1: placing carbon nanotubes in a mixed acid solution of H2SO4 / HNO3 with a volume ratio of 3:1, ultrasonicating at 80°C for 4 hours, and then washing, filtering and drying to obtain acid-treated carbon nanotubes; S2: Add the acid-treated carbon nanotubes to the acetone solution and stir evenly, then add the epoxy resin, continue stirring, and then heat to 150°C for reaction for 2 hours. After washing, filtering and drying, the pretreated carbon nanotubes are obtained. The mass ratio of the added epoxy resin to the acid-treated carbon nanotubes is 8:1. The other steps are the same as in Example 1.

[0048] Comparative Example Comparative Example 1 A highly flexible thermally conductive gasket, which differs from Example 1 in that the thermally conductive filler is only a core-shell aluminum ball filler, and no carbon nanotubes are added, and other steps are the same as Example 1.

[0049] Comparative Example 2 A highly flexible thermally conductive gasket, which differs from Example 1 in that the thermally conductive filler is only carbon nanotubes, and no core-shell aluminum ball filler is added, and other steps are the same as Example 1.

[0050] Comparative Example 3 A highly flexible thermally conductive gasket, which differs from Example 1 in that no cross-linked fiber is added, the cross-linked fiber in the raw material is replaced by vinyl MQ silicone resin of equal mass, and the other steps are the same as Example 1.

[0051] Comparative Example 4 A highly flexible thermally conductive gasket, which differs from Example 1 in that the terminal vinyl side chain vinyl silicone oil in the raw material is replaced by the side chain vinyl silicone oil DY-V411 of equal mass, and the other steps are the same as Example 1.

[0052] Comparative Example 5 A highly flexible thermally conductive gasket, which differs from Example 1 in that the terminal vinyl side chain vinyl silicone oil in the raw material is replaced by an equal mass of side chain vinyl silicone oil DY-V411, no cross-linked fiber is added, the cross-linked fiber in the raw material is replaced by an equal mass of vinyl MQ silicone resin, and the other steps are the same as Example 1.

[0053] Performance testing The high-flexibility thermally conductive gasket obtained in Examples 1-12 and Comparative Examples 1-5 was subjected to thermal conductivity, flexibility and other related performance test tests. Each group of tests was performed 3 times, and the average value of the 3 times was taken as the final result. The test results are recorded in Table 3.

[0054] 1. Thermal conductivity: Test the thermal conductivity of the thermal pad according to ASTM D 5470 standard; 2. Compression resilience: Test the resilience of the thermal pad according to ASTM D 575-91; 3. Hardness: Use the Shore hardness tester to test the hardness of the thermal pad according to the AM type; 4. Tensile strength: The tensile strength of the thermal pad is tested according to ASTM D 412 standard; 5. Electrical insulation performance: The breakdown voltage of the thermal conductive gasket is tested according to ASTM D 149 standard.

[0055] Table 3 According to the performance test results in Table 3, it can be seen that the thermal conductivity of a high-flexibility thermal conductive pad of the present application is 8.63-11.53 W·(m·K) -1 The Shore hardness is 28-38HA, the compression rebound rate is 74-91%, the tensile strength is 1.13-1.74MPa, and the breakdown voltage is 1.07-1.86Kv / mm. This shows that the high-flexibility thermal conductive gasket of the present application has excellent thermal conductivity and electrical insulation, and at the same time has good flexibility and compression rebound resilience, which can meet the needs of the thermal conductive gasket to better fit the uneven surfaces of some electronic components and efficiently transmit and dissipate heat.

[0056] According to the performance test results of Examples 1-5 and Comparative Example 3, it can be seen that the addition of cross-linked fibers further promotes the interaction between the silicone oil raw materials, which not only enhances the overall strength of the thermally conductive gasket, but also significantly enhances the flexibility of the heating gasket, so that the thermally conductive gasket can effectively disperse stress and prevent the gasket from breaking or deforming due to stress concentration.

[0057] It can be seen from the performance test results of Examples 1-4, Examples 6-10 and Comparative Example 2 that during the molding process of the thermally conductive gasket, the spherical aluminum filler can be evenly distributed between the carbon nanotubes, so that the thermally conductive gasket has better fluidity and dispersibility during the molding process, significantly reducing the problem of carbon nanotubes entangled and agglomerated with each other in the liquid slurry, reducing the interfacial thermal resistance, and at the same time enhancing the one-dimensional directional arrangement effect of the carbon nanotubes, forming a more effective heat conduction channel inside the thermally conductive gasket, thereby further improving the thermal conduction efficiency of the thermally conductive gasket.

[0058] Through self-passivation, metal aluminum microspheres are used as the core skeleton and wrapped with a dense alumina layer to form a core-shell aluminum ball filler. The excellent thermal conductivity of metal aluminum and the electrical insulation properties of ceramic materials are combined, so that the thermal conductive gasket has higher thermal conductivity while improving electrical insulation, increasing electricity safety and broadening the application field of thermal conductive gaskets.

[0059] According to the performance test results of Examples 1-4, Examples 11-12 and Comparative Example 1, it can be seen that the carbon nanotubes rely on their special one-dimensional linear structure to establish an efficient heat conduction channel network inside the thermal gasket, significantly improving the thermal conductivity efficiency of the thermal gasket.

[0060] Epoxy groups are introduced on the surface of carbon nanotubes, which significantly increase the compatibility between carbon nanotubes and silicone oil, silicone resin and cross-linked fibers through chemical reactions between chemical bonds, reducing the interfacial thermal resistance. At the same time, the dispersion of carbon nanotubes in the three-dimensional network structure formed in the thermal pad is further improved, significantly reducing the phenomenon of carbon nanotubes entangled and agglomerated with each other, further improving the thermal conductivity efficiency of carbon nanotubes as thermal conductive fillers and the mechanical properties of thermal conductive pads such as flexibility.

[0061] According to the performance test results of Example 1 and Comparative Examples 3-5, it can be seen that the present application selects terminal vinyl side chain vinyl silicone oil and terminal hydrogen silicone oil for cross-linking, which effectively improves the toughness of the gasket compared to the side chain vinyl silicone oil. In particular, the addition of cross-linked fibers to the network structure formed by the DY-V421 terminal vinyl side chain vinyl silicone oil has a better effect on improving flexibility and elasticity than the vinyl silicone oil DY-V411.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A highly flexible thermally conductive pad, characterized in that: The raw materials include, by weight, 23-46 parts of vinyl-terminated side-chain vinyl silicone oil, 9-15 parts of hydrogen-terminated silicone oil, 5-10 parts of vinyl MQ silicone resin, 11-17 parts of cross-linked fiber, 0.3-1.8 parts of platinum catalyst, 1-5 parts of cross-linking agent, 0.3-1.8 parts of inhibitor and 58-89 parts of thermal conductive filler; The thermal conductive filler comprises carbon nanotubes and core-shell aluminum ball fillers in a mass ratio of 1:(5-9).

2. The high-flexibility thermally conductive pad according to claim 1, characterized in that: The core-shell aluminum ball filler is a core-shell structure of spherical metal aluminum powder wrapped by aluminum oxide. The preparation method of the core-shell aluminum ball filler comprises the following steps: Spherical aluminum powder is added into anhydrous ethanol for ultrasonic treatment, and then centrifuged, dried and ground to form pretreated aluminum balls; The pretreated aluminum ball is heated to 300-500° C. in an air atmosphere and calcined for 6-8 hours to form a dense aluminum oxide layer on the surface of the pretreated aluminum ball, which is then cooled to obtain the product.

3. The high-flexibility thermally conductive pad according to claim 1, characterized in that: In parts by weight, the raw materials of the cross-linked fiber include 40-55 parts of polyethylene glycol, 15-25 parts of toluene diisocyanate, 0.2-0.6 parts of dibutyltin dilaurate and 5-10 parts of a chain extender.

4. The high-flexibility thermally conductive pad according to claim 3, characterized in that: The chain extender is an amino chain extender, and the amino chain extender is selected from any one or more combinations of 4,4'-methylene-bis(3-chloro-2,6-diethylaniline), ethylenediamine, dimethylthiotoluenediamine and triethylenetetramine.

5. The high-flexibility thermally conductive pad according to claim 4, characterized in that: The preparation method of the cross-linked fiber comprises the following steps: Mix polyethylene glycol and toluene diisocyanate, heat and stir at 80-100°C in an inert gas atmosphere, cool to 70-80°C, add an amino chain extender, continue stirring to perform chain extension and curing cross-linking reaction, and obtain a polyurethane prepolymer; Pour the polyurethane prepolymer into deionized water and stir to obtain a polyurethane stock solution; The polyurethane stock solution is matured, and then dry-spun to obtain cross-linked fibers.

6. The high-flexibility thermally conductive pad according to claim 1, characterized in that: The cross-linking agent is silane coupling agent KH-560.

7. The high-flexibility thermally conductive pad according to claim 1, characterized in that: The inhibitor is an acetylenic alcohol compound or a cyclic siloxane oligomer containing an olefin group.

8. A method for preparing a highly flexible thermally conductive gasket according to any one of claims 1 to 7, characterized in that: The following steps are involved: The carbon nanotubes and core-shell aluminum ball fillers are mixed to form a thermal conductive filler, and then mixed with terminal vinyl side chain vinyl silicone oil, terminal hydrogen silicone oil, vinyl MQ silicone resin, cross-linked fiber, cross-linking agent and inhibitor, stirred evenly, heated at 120-150° C., and vacuum reacted for 6-8 hours to obtain a blend; After the blend is cooled to room temperature, a platinum catalyst is added, stirred, and vacuum reacted for 10-15 minutes, and then hot vulcanized and formed at 120-130°C to obtain the product.

9. The method for preparing a highly flexible thermally conductive pad according to claim 8, characterized in that: The carbon nanotubes are pretreated as follows before being mixed with the core-shell aluminum sphere filler: The carbon nanotubes are placed in an acid solution and ultrasonicated at 60-80°C for 4-8 hours, and then washed, filtered and dried to obtain acid-treated carbon nanotubes; Add the acid-treated carbon nanotubes to the acetone solution and stir evenly, then add the epoxy resin, continue stirring, and then heat to 120-150°C for reaction for 2-3 hours. After washing, filtering and drying, the pretreated carbon nanotubes are obtained. The mass ratio of the epoxy resin added to the acid-treated carbon nanotubes is (80-120):1.

Citation Information

Patent Citations

  • Heat-conducting material for electronic product as well as preparation method and application of heat-conducting material

    CN114752218A

  • High-flexibility heat-conducting gasket and preparation process thereof

    CN116063852A

  • Prepn process of composite aluminium / alumina material with alumina coated metal aluminium

    CN1810419A

  • Highly heat-conductive resin composition

    JP1998204300A